2018
DOI: 10.1111/epi.14041
|View full text |Cite
|
Sign up to set email alerts
|

Extrahippocampal high‐frequency oscillations during epileptogenesis

Abstract: The current study aimed to investigate the spatial and temporal patterns of high-frequency oscillations (HFOs) in the intra-/extrahippocampal areas during epileptogenesis. Local field potentials were bilaterally recorded from hippocampus (CA1), thalamus, motor cortex, and prefrontal cortex in 13 rats before and after intrahippocampal kainic acid (KA) lesions. HFOs in the ripple (100-200 Hz) and fast ripple (250-500 Hz) ranges were detected and their rates were computed during different time periods (1-5 weeks)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 18 publications
(53 reference statements)
4
38
2
1
Order By: Relevance
“…The latter experiments were performed during the latent period of epileptogenesis (1‐4 weeks after status). Of note, their results do show a slight down‐trend in the frequency of SWRs and FRs at the end of their recording period (week 5) . Given that we are looking at dramatically different time points, and that our area of interest is outside of the origin of status (ie, the primary focus), we do not consider our results contradictory.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…The latter experiments were performed during the latent period of epileptogenesis (1‐4 weeks after status). Of note, their results do show a slight down‐trend in the frequency of SWRs and FRs at the end of their recording period (week 5) . Given that we are looking at dramatically different time points, and that our area of interest is outside of the origin of status (ie, the primary focus), we do not consider our results contradictory.…”
Section: Discussionmentioning
confidence: 70%
“…Although we show an overall decrease in SWR frequency in epileptic mice, there are other studies that have shown the opposite. Notably, in the intrahippocampal kainate model of TLE, the rats that go on to develop epilepsy exhibit increased numbers of both ripples (similar to our SWRs) and FRs in the hippocampus . The latter experiments were performed during the latent period of epileptogenesis (1‐4 weeks after status).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…One example is research involving seizures and epilepsy models in which electrophysiological parameters, such as high-frequency oscillations, which are known to be associated with the disease are studied without regard to the possible effects of surgery. Moreover, these surgeries typically involve specific brain areas, such as the hippocampus and cortex; these areas contain circuits that are associated with the cognitive process through theta and gamma rhythms and ripple events and with specific physiological behaviours, such as the sleep-wake cycle [10][11][12]. Most of these surgeries involve the implantation of electrodes or microelectrodes into the brain for the purpose of recording electrical signals and/or the implantation of guide cannulas that are used to insert dialysis probes or fine needles for drug administration [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%